Expanding Consciousness, Integral Consciousness, and Conscious Evolution in Paule Marshall's Fiction - Castro-Borrego, Silvia Pilar (Universidad de Zaragoza, 2022)
Marshall’s literary concerns link with key issues of the black diaspora such as black consciousness and the search for wholeness. This two preoccupations of the author connect in a straightforwardly manner with the pioneer work on the multiple studies on consciousness being brought forward internationally at present by scientists such as physicist Peter Russell, nurse Margaret Newman, philosopher Ken Wilber and psychologist Paloma Cabadas. In this essay, I contend that Marshall’s characters undergo a leap of consciousness that becomes a first step into their necessary search for wholeness. Her writings become part of the Black Consciousness Movement, by contributing to the development of epistemologies that have their roots in “the workable past,” creating emancipatory knowledge for African people and their descendants. The methodology employed to read Marshall’s novels follows the conscious evolution paradigm brought forward by psychologist Paloma Cabadas, and the integral consciousness model proposed by Ken Wilber. Both models offer valid routes to analyze Marshall’s characters in the light of Newman’s concept of the expanding of consciousness.
Keywords: Marshall, Paule - Crítica e interpretación; Expanding Consciousness; Integral Consciousness; Conscious Evolution; Black Consciousness; Wholeness